2020
DOI: 10.1108/cg-07-2019-0206
|View full text |Cite
|
Sign up to set email alerts
|

Gender diversity influence on board effectiveness and business performance

Abstract: Purpose The purpose of this paper is to analyze the mediating role of board effectiveness (understood as the capacity to efficiently manage and control all functions to guarantee the company’s prosperity) in the relationship between board diversity and firm performance. Design/methodology/approach The authors use partial least squares methodology to test the direct and indirect relationships between gender diversity in boards of directors and business performance. Findings Although the relationship between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 70 publications
(92 reference statements)
3
45
1
Order By: Relevance
“…The empirical results show that women on corporate boards contribute to effective board processes and outcomes when their proposed ideas during board meetings are accepted by other board members, implemented by the management and impact positively on organizations' outcomes such as enhanced financial, product and staff outcomes. This finding seems to give credence to previous results by Srinidhi et al (2020) and Arioglu (2020) but inconsistent with prior studies that found negative outcomes (Comi et al, 2020;Martinez-Jimenez et al, 2020), or no significant impact (e.g., Arora & Singh, 2020;Zajiji et al, 2020). This result, from the perspectives of the resource dependence and resource-based theories, suggests that female directors of organizations are vital resources because they are sources of wise counsel, useful ideas and advice (Hillman & Dalziel, 2003) for making positive organizational changes or impacts.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…The empirical results show that women on corporate boards contribute to effective board processes and outcomes when their proposed ideas during board meetings are accepted by other board members, implemented by the management and impact positively on organizations' outcomes such as enhanced financial, product and staff outcomes. This finding seems to give credence to previous results by Srinidhi et al (2020) and Arioglu (2020) but inconsistent with prior studies that found negative outcomes (Comi et al, 2020;Martinez-Jimenez et al, 2020), or no significant impact (e.g., Arora & Singh, 2020;Zajiji et al, 2020). This result, from the perspectives of the resource dependence and resource-based theories, suggests that female directors of organizations are vital resources because they are sources of wise counsel, useful ideas and advice (Hillman & Dalziel, 2003) for making positive organizational changes or impacts.…”
Section: Discussioncontrasting
confidence: 81%
“…Likewise, in Instanbul, Arioglu (2020) suggested that women on corporate boards improve corporate financial outcomes in men-dominated cultural societies because women ensure better monitoring and bring enriched ideas and perspectives, which inject creativity and innovation in board process by improving decision-making in the boardroom. On the contrary, Martinez-Jimenez et al (2020) found that women on corporate boards have a negative effect on board effectiveness (strategic control, organizational innovation and decision-making), but they have insignificant effect on business performance. Besides, some people argue that diversity breeds conflict, which, in turn, can adversely affect the speed of decision-making, by complicating and slowing decision-making (Triana et al, 2014).…”
Section: Contributions Of Female Directors To Board Processes and Outcomesmentioning
confidence: 92%
See 1 more Smart Citation
“…However, it has had little to no effect on high-level management positions. As such, a government proposal as the likes of implementing a legal quota to increase the number of women on management boards is necessary (Lazzaretti et al, 2013;Martinez-Jimenez, Hernández-Ortiz, & Fernández, 2020). Few countries have accomplished this, even with attenuating inequality levels in so-called first-world countries.…”
Section: Corporate and Public Policiesmentioning
confidence: 99%
“…This phenomenon is becoming a trend of recent years in Europe as means to accelerate the gender equality process since the issue has not considerably advanced regarding positions of power and management, especially in private companies. It is the case even after the intensification of discussions on issues such as the glass ceiling, discrimination, and others related to existing gender inequality (Nekhili & Gatfaoui, 2013;Cohen et al, 2020;Martinez-Jimenez et al, 2020).…”
Section: Corporate and Public Policiesmentioning
confidence: 99%